2018
DOI: 10.1155/2018/9547613
|View full text |Cite|
|
Sign up to set email alerts
|

Role of Oxidative Stress in Pathophysiology of Nonalcoholic Fatty Liver Disease

Abstract: Liver steatosis without alcohol consumption, namely, nonalcoholic fatty liver disease (NAFLD), is a common hepatic condition that encompasses a wide spectrum of presentations, ranging from simple accumulation of triglycerides in the hepatocytes without any liver damage to inflammation, necrosis, ballooning, and fibrosis (namely, nonalcoholic steatohepatitis) up to severe liver disease and eventually cirrhosis and/or hepatocellular carcinoma. The pathophysiology of fatty liver and its progression is influenced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
384
0
9

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 514 publications
(437 citation statements)
references
References 117 publications
3
384
0
9
Order By: Relevance
“…The latter finding is principally associated with the abolishment of HFD‐induced activation of the redox‐sensitive factor NF‐κB, as a consequence of the normalization of the oxidative status of the liver, in addition to the increased availability of resolvins avoiding inflammatory development. Collectively, these findings point toward oxidative stress as an important acting factor in the development in HFD‐dependent liver steatosis and establishment of a pro‐inflammatory state, which can further increase in NASH to progress into fibrosis and cirrhosis . Hence, abrogation of hepatic steatosis by combined DHA and HT would represent a crucial therapeutic strategy eluding disease progression into stages lacking efficacious handling at present time …”
Section: Discussionmentioning
confidence: 99%
“…The latter finding is principally associated with the abolishment of HFD‐induced activation of the redox‐sensitive factor NF‐κB, as a consequence of the normalization of the oxidative status of the liver, in addition to the increased availability of resolvins avoiding inflammatory development. Collectively, these findings point toward oxidative stress as an important acting factor in the development in HFD‐dependent liver steatosis and establishment of a pro‐inflammatory state, which can further increase in NASH to progress into fibrosis and cirrhosis . Hence, abrogation of hepatic steatosis by combined DHA and HT would represent a crucial therapeutic strategy eluding disease progression into stages lacking efficacious handling at present time …”
Section: Discussionmentioning
confidence: 99%
“…The overproduced reactive oxygen species (ROS) will make the antioxidant system incapable of clearing and oxidative stress. Meanwhile, abnormal oxidation of fat deposition is aggravated by the massively generated peroxidation, resulting in more serious lipid degeneration (Masarone et al, ; Spahis et al, ; Videla, Rodrigo, Araya, & Poniachik, ). In addition, previous studies have shown that the level of ROS was elevated in T2DM mice, in which the antioxidant capacity was reduced (Lu et al, ; Lu et al, ; Lu et al, ; X. Zhu, Cheng, et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial β‐oxidation breaks down FFAs but produces ROS, which causes liver damage. FFAs also induce endoplasmic reticulum (ER) stress, which is caused by accumulation of unfolded and misfolded proteins, and ER stress is another potent source of ROS . Melatonin has strong antioxidant effects and can be utilized to protect the liver from NAFLD or fatty acid‐induced liver damage.…”
Section: Functional Roles and Therapeutic Potentials Of Melatonin Andmentioning
confidence: 99%